2015
DOI: 10.1371/journal.pone.0119781
|View full text |Cite
|
Sign up to set email alerts
|

LOX Expression and Functional Analysis in Astrocytomas and Impact of IDH1 Mutation

Abstract: Lysyl oxidase (LOX) is involved in vital biological processes such as cell motility, cell signaling and gene regulation. Deregulation of this protein can contribute to tumor formation and progression. Although it is known that LOX is involved in invasion, proliferation and tumor migration in other types of tumors, studies of LOX in astrocytomas of different grades are scarce. The purpose of our study was to characterize LOX, BMP1 and HIF1A expression by real-time PCR in astrocytomas with WHO grades I to IV com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 64 publications
4
33
0
1
Order By: Relevance
“…MMPs break down fibrous ECM structures, like collagen, to create reorganization within the tumor, and they lead to changes in physical properties. Traditionally, increases in MMP expression and LOX expression are associated with high-grade tumors (24,25). However, in the context of optic nerve glioma, we saw a decrease in MMP-2 and no change in LOX, which suggests less breakdown of collagen fibers (a greater degree of collagen cross-linking).…”
Section: Ecm-modifying Enzyme Expression Is Altered In Glioma-bearingmentioning
confidence: 60%
“…MMPs break down fibrous ECM structures, like collagen, to create reorganization within the tumor, and they lead to changes in physical properties. Traditionally, increases in MMP expression and LOX expression are associated with high-grade tumors (24,25). However, in the context of optic nerve glioma, we saw a decrease in MMP-2 and no change in LOX, which suggests less breakdown of collagen fibers (a greater degree of collagen cross-linking).…”
Section: Ecm-modifying Enzyme Expression Is Altered In Glioma-bearingmentioning
confidence: 60%
“…High expression of LOX is related to worse outcome in some cancer, such as astrocytomas, non-small lung cancer and GC. [37][38][39] Notably, the protein LOX has also been shown to have antitumor activity in several cancer types, including GC, lung cancer and nasopharyngeal carcinoma. [40][41][42] In this study, we also found that the expression of LOX was significantly increased in tumor tissues compared to peritumoral tissues.…”
mentioning
confidence: 99%
“…For example, Agra et al (2013) showed that EWS/FLI1 downregulates LOX expression and that, remarkably, LOX propeptide exhibits tumor suppressor activities in Ewing tumor cells. Da Silva et al (2015) confirmed that LOX plays an important role in migration and angiogenesis in diffusively infiltrative astrocytomas, and LOX expression is influenced by IDH1 mutational status. Furthermore, cancer progression is closely related to its microenvironment, such as the extracellular matrix around the tumor (Allen and Louise Jones, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…LOX is an extracellular copper-containing enzyme which catalyzes the crosslinking of collagen and elastin, and plays a critical role in extracellular matrix organization (da Silva et al, 2015). Increasing evidence suggests that LOX is involved in tumor progression and metastasis, while its role in tumorigenesis is still contradictory (Boufraqech et al, 2015).…”
Section: Introductionmentioning
confidence: 99%